Exercise Influence on Hippocampal Function: Possible Involvement of Orexin-A - Chieffi, Sergio; Messina, Giovanni; Villano, Ines; Messina, Antonietta; Esposito, Maria; Monda, Vincenzo; Valenzano, Anna; Moscatelli, Fiorenzo; Esposito, Teresa; Carotenuto, Marco; Viggiano, Andrea; Cibelli, Giuseppe; et al. (Frontiers in Physiology, 2017)
Structural and functional changes of the brain occur throughout life to cope with new demands. This review examines the main findings obtained from two significant lines of research. The first line of research encompasses the studies showing the beneficial effects of the physical exercise on hippocampal neurogenesis and cognition. The enhancement of the cognitive abilities produced by exercise represents a valuable and promising tool for preventing cognitive decline associated with aging. The second line of research refers to the study of the hypocretin-1/orexin-A influence on hippocampus functioning. Recent research suggests that hypocretin-1/orexin-A increases during exercise and it plays a significant role at the level of the hippocampus in regulating social cognition and mood.